THE ROLE OF LACTOBACILLUS CASEI AND LACTOBACILLUS ACIDOPHILLUS TO DECREASE THE BIOLOGICAL EFFECTS OF POTASSIUM BROMATE IN RATS - Mohammed, M. J.; Mahdi, M. S.; Jameel, A. H.; Thalj, K. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was conducted to investigate the ameliorative effect of lactic acid bacteria Lactobacillus casei and Lactobacillus acidophilus against Potassium bromate (25, 50) mg / kg toxicity by some physiological indicators in 35 of female rats after 21 days. The animals were divided into 7 groups within each group 5 animals weighted 140 – 155 g. The results showed a significant decrease (P<0.05) in value of Red blood cells (RBC), hemoglobin (Hb), White blood cells (WBC), Lymphocyte (LYM) and Platelets (PLT), While increasing the values of Granules (GRN). Also found that the addition of Potassium bromate Potassium bromate led to increase in cholesterol, triglyceride (TG), Low Density Lipoprotein (LDL) and blood glucose, while decreased the values of High Density Lipoprotein (HDL) for rats groups with increasing the concentration of Potassium bromate compared with control group. The addition of two types of lactic acid bacteria L. casei and L. acidophilus with Potassium bromate showed a positive effect to reducing the negative effect of Potassium bromate on blood and lipid profile parameters compared with the control group and Potassium bromate group. It is concluded that the lactic acid bacteria has protective effects and reduces the effects that Potassium bromate.